Perspektif Hukum Internasional Terhadap Perlindungan HAM Aktivis Kemanusiaan - Medyline Agnes Elias; Josina Augusthina Yvonne Wattimena; Veriana Josepha Rehatta (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: In the midst of the territorial conflict between Israel and Palestine and various human rights violations that also occurred in the conflict, a humanitarian activist named Rami Aman from Gaza was arrested by Hamas based on a report by a former Amnesty worker.Purposes of the Research: The aim of the author is to find out about the regulation of protection of humanitarian activists in international law instruments and the legal remedies that Amnesty International can take in protecting human rights for humanitarian activists.Methods of the Research: The method used in this research, namely normative legal research methods carried out by using literature study where by examining library materials and secondary data in assessing the prevailing legal norms, which are then presented descriptively and conclusions are given.Results of the Research: The results of the research obtained from this writing are that the protection of human rights from humanitarian activists has been regulated in international legal instruments, but these laws are soft law so they are not legally binding. These legal instruments can become hard law and legally binding if adopted in national law. As a non-governmental organization, Amnesty International can protect human rights of the humanitarian activists with the rights it derives from the consultative status it obtains and press the government concerned and pay public attention to these problems through campaigns and actions and most importantly for Amnesty International to work according to the principles it has.